Influence of the Potential Carbon Sources for Field Denitrification Beds on Their Microbial Diversity and the Fate of Carbon and Nitrate - Grießmeier, Victoria; Gescher, Johannes (Frontiers in Microbiology, 2018)
Nitrogen based eutrophication of ecosystems is a global problem that gains momentum through a growing global population. The water quality of nitrate or ammonium contaminated rivers and streams cannot always be amended in centralized waste water treatment plants. Field denitrification plants were suggested as a solution for a decentralized reduction of nitrate to dinitrogen. Here, stable and cheap organic carbon sources serve as carbon and electron source for a microbial community. Still, our knowledge on the impact of these organic carbon sources on the development and diversity of these cultures is sparse. Moreover, the stability of these denitrification plants at different nitrate loading rates especially in the higher concentration regime were not tested so far. In this study, we compare the fate of carbon and nitrogen as well as the microbial community of wood pellet (pressed sawdust), wheat straw and wood chips based laboratory denitrification reactors. Our study reveals that the diversity and composition of the community is strongly dependent on the carbon source. The diversity decreased in the order wood chips, wheat straw, wood pellets. The three reactor types were characterized by different nitrate reduction kinetics and were affected differently by high nitrate loading rates. While the nitrate reduction kinetics were negatively influenced by higher nitrate doses in the wheat straw reactors, wood pellets as carbon source sustained the opposite trend and wood chips lead to an overall slower but concentration independent nitrate reduction rate. Counterintuitively, the concentration of soluble organic carbon was highest in the wood pellet reactors but methane emission was not detectable. This is corroborated by the microbial diversity data in which methanogenic species were highly underrepresented compared to the other two reactor types. In contrary, the methane emissions in the wheat straw and wood chip reactors were comparable to each other.